Designing Air Quality Detection Systems with Over-the-Air Firmware Update Methods for Performance Enhancement - Nanda Syaputra; Ade, Ade Silvia Handayani; Taqwa, Ahmad Taqwa (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
Implementing the Over-The-Air (OTA) system, which facilitates wireless and remote updates of software or firmware through internet connectivity, offers a significant advantage by saving both time and effort. This approach allows for firmware updates to be performed directly from any location, eliminating the need to physically visit each device. This is especially advantageous in the manufacturing of air quality monitoring devices, where adjustments to programs and software are often needed, particularly with seasonal changes. Updating firmware manually on numerous devices can be a time-consuming and labor-intensive process. To address this issue, the proposed device will be designed to support air quality readings and will utilize an internet connection to enable virtual firmware updates. The device will periodically check its program storage for new firmware versions. When a new version is detected, the device will automatically download and install the latest firmware available. This process reduces the need for manual intervention and improves operational efficiency. Additionally, deploying multiple devices across a large area is crucial for ensuring comprehensive coverage. This approach not only simplifies maintenance but also enhances the operational management of air quality monitoring systems. By leveraging OTA technology, the process of updating devices becomes more streamlined, scalable, and efficient, contributing to more effective environmental monitoring and management.